2019
DOI: 10.1088/1748-3190/ab04d1
|View full text |Cite
|
Sign up to set email alerts
|

A variable stiffness gripper based on differential drive particle jamming

Abstract: Compared with rigid grippers, soft grippers show fantastic adaptability and flexibility in grasping irregularly shaped and fragile objects. However, the low stiffness of the soft actuator limits the scope of applications. Particle jamming has emerged as an important method to adjust the stiffness of soft grippers. This paper proposes a novel particle jamming mechanism based on the differential pressure drive. With the differential drive particle jamming mechanism, a soft actuator is designed, which is characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 32 publications
0
49
0
1
Order By: Relevance
“…Jamming pressure is the most commonly modified metric across all tests (likely due to most researchers using pneumatic actuation, which allows for simple pressure variation). Numerous studies [7,10,21,22,25,31] showed the holding force, or maximum held weight, increasing alongside actuation pressure, from 0 to 450 kPa, across diverse grain, membrane and actuation compositions. Kapadia et al [10] found that the holding force was independent of ambient pressure across two orders of magnitude, and tests at various ambient pressures showed the holding force was more sensitive to increases in actuation pressure between 30 and 85 kPa than 85 and 450 kPa.…”
Section: Grasp Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Jamming pressure is the most commonly modified metric across all tests (likely due to most researchers using pneumatic actuation, which allows for simple pressure variation). Numerous studies [7,10,21,22,25,31] showed the holding force, or maximum held weight, increasing alongside actuation pressure, from 0 to 450 kPa, across diverse grain, membrane and actuation compositions. Kapadia et al [10] found that the holding force was independent of ambient pressure across two orders of magnitude, and tests at various ambient pressures showed the holding force was more sensitive to increases in actuation pressure between 30 and 85 kPa than 85 and 450 kPa.…”
Section: Grasp Testingmentioning
confidence: 99%
“…All pertinent studies showed that stiffness increased alongside jamming actuation pressure for granular, layer and hybrid jamming. This was across load vs. displacement [8,15,16,26,37,38,40,42,[44][45][46][47]56,57,65], bending angle [6,21,25,31,38], applied moment [15,16,21,26,38,44,57] and rotational stiffness tests [21,25,30,31]. Studies commonly positioned beam, cylindrical, and finger actuators as cantilever beams [8,9,15,26,32,38,46,47,58].…”
Section: Stiffness Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, various mechanical of variable stiffness have developed, such as heat‐sensitive material [7, 8], magnetorheological (MR) or electrorheological (ER) fluid [9, 10], low‐melting‐point alloys (LMPAs) [11] and jamming [12, 13]. Among them, heat‐sensitive materials include conductive polylactic acid (CPLA) [14], liquid metal, shape memory polymer (SMP) and so on, which are soft when heated and become stiff when cooled.…”
Section: Introductionmentioning
confidence: 99%
“…(3) 堵塞机构还可与流体驱动结合: WALL 等 [14] 将堵塞机构与气体驱动器相结合, 提出变刚度手指。 WEI 等 [15] 提出了可自适应抓取的变刚度软体夹持 器,对物体适形后,通过真空作用可迅速固化使手 指保持既有形态,刚度提高 10 倍以上。BROWN 等 [16] 设计了一款新型软体移动机器人,在流体状态 球形机器人表面布置多个堵塞单元,通过堵塞部分 单元格,实现滚动运动。其他较有创新的堵塞机构 包括:JIANG 等 [17] 提出了一种基于差压驱动的新型 颗粒阻塞机构。WANG 等 [18] 提出了一种新型层阻塞 变刚度技术。 YAO 等 [19] 设计了一种气动式可变刚度 的软体机械臂模块,实现了软体机械臂的模块化。 WANG 等 [20] 对软体机器人目前的发展现状进行了 系统的总结,并提出可变刚度研究方向可能是未来 软体机器人研究新的突破点。 综上所述,堵塞机构多应用小尺寸颗粒材料, 由于小颗粒易发生变形和重新排列,可能导致不同 运动形态和变刚度失效, 降低了机构重复定位精度, 甚至定位错误。科研人员目前多试图从试验的角度 去分析影响堵塞机构的主要因素 [21][22][23]…”
unclassified